PHILOSOPHICAL ASPECTS OF SUFI VIEWS ABDURAHMAN JAMI - Shodiyev Rustam Toxirovich (Journals Park Publishing, 2022)
The article describes the views of Abdurahman Jami, a great figure of Persian-Tajik literature, a prominent representative of the Naqshbandi sect, on Sufi philosophy. Some works of Abdurrahman Jami have a religious and philosophical content, in which the poet interprets a number of issues of Islamic religion and Eastern philosophy from his point of view. Jami's belief in Sufism is pure and perfect.
Keywords: Islamic religion, Sufism, Muslim East, Naqshbandi order, Khurasan